CA-15-3 And Breast Cancer - B.PRABASHEELA,; R.ARIVAZHAGAN, (International Journal of Pharma and Bio Sciences, 2011)
Tumor Markers are a potential powerful means of obtaining information about cancer.CA 15-3 is a well established tumor marker for early detection of recurrent breast cancer .Blood samples were investigated for CA 15-3 level in 50 histopathologically proven breast cancer patients of which 30 patients are untreated and 20 had under gone primary surgery in comparison with 50 normal healthy persons (control) of similar average age limit and body mass. Serum levels of CA 15-3 were significantly in breast cancer patient (p <0.05).